TINJAUAN YURIDIS PENGESAHAN ANAK YANG LAHIR DILUAR NIKAH - Kholis Sulung P (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACK Marriage is a medium to achieve the objectives of Islamic Shari'a, one of which is an active-offensive form of hereditary protection (high an-nasl), for the sake of preserving offspring and avoiding esyubhatan (polluted) in the determination of the nasab. Therefore, the distribution of human biological desires must be within the boundaries of religious corridors, so as to avoid the trappings of immoral acts or adultery outside the marriage fence. The presence of a child in the household is very desirable. Children are hereditary offenders, where legitimate offspring that are recognized by themselves, society, state, and legitimate according to religion are certainly expected. However, in reality, often encountered a situation where the presence of a child in a family is not always happy. This usually happens when a child is born outside legal marriage. The birth of a child outside marriage is not only caused by an extramarital relationship. A woman in certain circumstances can also give birth to a child outside marriage if the marriage takes place in a customary manner and is not registered in accordance with the provisions of the applicable laws and regulations. Seeing the case of out-of-wedlock children currently developing in the community will be limited to the recognition and approval of out-of-wedlock children who are subject to the Civil Code.The method used in this study is a normative juridical method, data or information obtained through library research. From the results of library research secondary data is obtained which includes primary legal materials, secondary legal materials and tertiary legal materials. The problems that the authors discuss in this thesis are the process of ratification of children born out of wedlock and the legal status of children born out of wedlock after ratification.Based on the results of the study it can be concluded that the requirements and the process of recording the recognition and endorsement of children can be done at the Population and Civil Registry Office. Requirements for obtaining a certificate of recognition and endorsement of a child are a certificate from the RT / RW that is known by the village head / lurah, a photocopy of a birth certificate, a photocopy of a KTP, and KK as well as a certificate of a religious marriage. The requirements for those who are Muslim are added to the verdict of recognition or endorsement from the Religious Court and Article 43 paragraph (1) of the Marriage Law explains that a child out of wedlock is a child born from an illegitimate marriage and the child only has a civil relationship with the mother who gave birth to him or his mother's family. But this status will change after the process of recognition and endorsement through a court decision to officially have a man as his father and a woman who gives birth as his mother, so thus the child has a civil relationship with his father and has a civil relationship with the mother who gave birth to a child and has a relationship of rights and obligations between the child and the father and mother who gave birth as parents to the child born. Keywords: Child Endorsement, Marriage, Children Out of Marriage